The art of war for small business : defeat the competition and dominate the market with the masterful strategies of Sun Tzu - Sheetz-Runkle, Becky (AMACOM--American Management Association, 2014)
Sun Tzu's ancient The Art of War has inspired military, political, and business leaders across the world with its brilliant strategies for prevailing against opponents. At the core of this classic treatise is the message that sledgehammer approaches can backfire, and size alone does not guarantee wins. Strategy, positioning, planning, leadership--all play equally significant roles, making Sun Tzu's teachings perfect for small business owners and entrepreneurs entrenched in fierce competition for customers, market share, talent ... for their very survival. The Art of War for Small Business is the first book to apply Sun Tzu's wisdom to the small business arena. Featuring inspiring examples of entrepreneurial success, the book's 12 timeless lessons reveal how to: * Choose the right ground for your battles * Prepare without falling prey to paralysis * Leverage strengths while overcoming limitations * Strike competitors' weakest points and seize every opportunity * Focus priorities and resources on conquering key challenges * Go where the enemy is not * Build and leverage strategic alliances. Big companies may deploy overwhelming forces, but small companies can outsmart, outmaneuver, and outstrategize larger adversaries to capture crucial sectors, serve unmet needs, and emerge victorious.